Bivariate Positive Operators in Polynomial Weighted Spaces - Octavian Agratini (Abstract and Applied Analysis)
This paper aims to two-dimensional extension of some univariate positive approximation processes expressed by series. To be easier to use, we also modify this extension into finite sums. With respect to these two new classes designed, we investigate their approximation properties in polynomial weighted spaces. The rate of convergence is established, and special cases of our construction are highlighted.